2009
DOI: 10.1098/rstb.2009.0184
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional effects on oocyte and embryo development in mammals: implications for reproductive efficiency and environmental sustainability

Abstract: The environment in which a breeding female lives prior to conception and during the early stages of her pregnancy has striking effects on oocytes developing in the ovarian follicle and on early embryos in the reproductive tract. Of the various environmental factors known to affect oocyte and embryo development, altered nutrition during this critical period has been particularly well studied. Alterations in the quantity of food consumed or the composition of the diet imposed solely during the pre-mating period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(127 citation statements)
references
References 66 publications
3
119
0
5
Order By: Relevance
“…Both animal and human studies have shown that the preconception environment may alter oocyte maturation 69 with maternal obesity affecting the metabolism of the developing ova and early offspring growth 70,71 . Because mitochondrial DNA is only passed on through the maternal line, oocyte mitochondrial DNA may provide a further sex-specific intergenerational mechanism.…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…Both animal and human studies have shown that the preconception environment may alter oocyte maturation 69 with maternal obesity affecting the metabolism of the developing ova and early offspring growth 70,71 . Because mitochondrial DNA is only passed on through the maternal line, oocyte mitochondrial DNA may provide a further sex-specific intergenerational mechanism.…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…Vinsky et al (2006) and Patterson et al (2011) observed similar losses in sows submitted to feed restriction during lactation. Several authors suggest that the nutritional and metabolic changes in lactating sows may have deleterious effects on dam biology, with negative impacts on follicle development, and consequently on embryo development and on the number of piglets born in the next litter (Foxcroft et al, 2007;Ashworth et al, 2009;Quesnel, 2009;Schenkel et al, 2010;Hoving et al, 2011). According to Foxcroft et al (2009), the mechanisms affecting fertility may involve hormonal changes, as well as epigenetic changes and/or changes in the expression of genes related to embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…One well-known example of this "environmental buffering" is the heat-shock response. Although the influence of diet on reproductive capability has been well demonstrated in Drosophila melanogaster, Caenorhabditis elegans, and mammals (Ashworth et al 2009;Ables et al 2012;Hubbard et al, 2013), to our knowledge, mechanisms by which gametogenesis efficiency is maintained under suboptimal environments have not been explored. Our study suggests the hypothesis that differential partitioning of cell fate within a yeast community provides environmental buffering-here termed the DPEB hypothesis.…”
Section: Discussionmentioning
confidence: 99%